English in Uniform - Kompara Lukančič, Mojca (University of Maribor Press, 2021)
The monograph titled English in Uniform is composed of 8 chapters that focus on terminological and lexical issues, a grammatical overview, the principles of the constitution, the introduction into national and international organization, the introduction to the political system in the UK, the USA, the EU and Slovenia, the concepts of Human Rights and Fundamental Freedoms, and correspondence. The scope of the monograph is to give to the students, teachers, linguists, translators, and those interested in the LSP filed of security and justice, an insight in the discussed topics.